The impact peer Review Applicaiton on Reducing Audit Risk – A field study on the accounting auditing offices operating in Khartoum state – - Osman, Ibrahim Yagub Ismail; Yousaf, Aisha Mousa Mohammed; Grayb, Abeer Abdallah Mohammed (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to identify the peer review and the extent of its use in the audit offices, and then to know its impact on reducing risks in the audit, the study used the descriptive analytical method to collect and analyze the study data based on primary sources such as the questionnaire where the study was applied in the audit offices in Khartoum, the study reached Results: Most of the accounting and auditing offices operating in Khartoum state are interested in implementing peer review,There is a positive and statistically significant relationship between risks and the inverse relation between the review of the report and the discovery risks. The study concluded with recommendations including the need to pay attention to the accounting and audit offices operating in Khartoum State to apply peer review to include all offices in Sudan due to their importance in improving the quality of audit.
Keywords: Peer review; Inherent risks; Control risks; Detection risks